ANALISIS PENGGUNAAN BOM FOSFOR PUTIH DALAM PERANG ISRAEL - PALESTINA DAN LEBANON MENURUT HUKUM HUMANITER INTERNASIONAL: THE USE OF WHITE PHOSPHORUS BOMB ANALYSIS IN ISRAEL-PALESTINE AND LEBANON WARFARE UNDER INTERNATIONAL HUMANITARIAN LAW - Wibowo, Aji; Kusuma, Muhammad Aziz Eka Surya; Maulana, Rafli Syah; Gunawan, Suryanto (Fakultas Hukum Universitas Trisakti, 2024)
This research reviews the use of white phosphorus bombs carried out through artillery attacks with 115 mm White Phosphorus Artillery Projectiles by the Israel Army against populated areas in the Gaza City port area and rural areas on the Israel-Lebanon border. This research aims to find out how the dangerous effect that can be caused by the use of white phosphorus bombs in war which is prohibited from being used in war contained in Article 23 paragraphs (1), (2) and (4) of the 1907 Hague Convention and to find out what kind of impact resulted from the use of white phosphorus bombs. The type of research used in this article is qualitative research. The data sources of this research are the results of documents and actions related to the use of white phosphorus bombs by the Israel army in the Israel-Palestine and Lebanon wars. The result of the research is that Israel has violated the basic principles of international humanitarian law becouse Israel uses white phosphorus in war which white phosphorus bombs are very dangerous to humans which can cause injuries that are difficult to cure and if exposed to large amounts of exposure, it can damage the liver or kidneys with severe damage.